The Ancient World on the Victorian and Edwardian Stage - Richards, J. author. aut Link
XI, 267 p. 1 illus.
Keywords: The first study of the depictions of the Ancient World on the Victorian and Edwardian stage, this book analyzes plays set in and dramatising the histories of Greece, Rome, Egypt, Babylon and the Holy Land. In doing so, it seeks to locate theatre within the wider culture, tracing its links and interaction with other cultural forms.